1991
DOI: 10.1038/349329a0
|View full text |Cite
|
Sign up to set email alerts
|

Rejection of class I MHC-deficient haemopoietic cells by irradiated MHC-matched mice

Abstract: Irradiated MHC-heterozygous mice often reject bone marrow cells transplanted from one of the homozygous parental strains, a phenomenon ('hybrid resistance') that appears to violate the laws of transplantation. Rejection of parental and allogeneic marrow cells also differs from conventional T cell-mediated rejection mechanisms as it is effected by NK1.1+ cells. To account for the unusual specificity of bone marrow rejection, it has been proposed that NK1.1+ cells destroy marrow cells that fail to express the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
260
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(281 citation statements)
references
References 26 publications
11
260
2
Order By: Relevance
“…Studies in mice demonstrated that NK cells vigorously reject both neoplastic and normal, healthy cells lacking one or more self MHC class I ligands [4,5,[21][22][23]. Adoptive transfer of activated NK cells with missing-self-reactivity against the host can reduce GVH disease, promote BM engraftment and provide graft-versustumor responses [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mice demonstrated that NK cells vigorously reject both neoplastic and normal, healthy cells lacking one or more self MHC class I ligands [4,5,[21][22][23]. Adoptive transfer of activated NK cells with missing-self-reactivity against the host can reduce GVH disease, promote BM engraftment and provide graft-versustumor responses [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, NK cells that express MHC class I-specific inhibitory receptors have been found to be functionally reactive, but NK cells that lack MHC class I-specific inhibitory receptors are hyporeactive to the same stimuli and do not exhibit cytotoxicity to MHC class I-deficient target cells (27,28). Likewise, inhibitory receptor-expressing NK cells of MHC class I-deficient patients (29)(30)(31) and NK cells of β 2 m -/- (32)(33)(34), TAP -/- (31,35), or MHC-deficient (34, 36) mice do not kill MHC class I-deficient normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated by other groups that NK cells recognize and lyse syngeneic lymphoblasts and bone marrow cells from ␤2-microglobulin Ϫ/Ϫ or TAP Ϫ/Ϫ donors. [71][72][73] In contrast, data from ␤2-microglobulin-deficient mice showed that skin grafts from those deficient mice were not recognized by NK cells. 64 The same may be true for the human immune system however, this still must be elucidated in vivo.…”
Section: Discussionmentioning
confidence: 95%